Sistem Informasi Akuntansi Pada Proses Pembelian Dan Penjualan Di Minimarket Lestari Berbasis Web - Rio Priantama; Neneng Herlina (NUANSA INFORMATIKA, 2011)
Accounting Information Systems of Purchasing and Sales Process functions to manage the company's financial data.This study is aimed to delevop an accounting information system of purchasing and sales process that can handle the data management of large amounts and uncontrolled goods, especially in Lestari Minimarket. Main concepts in the designing and developing Accounting information systems of purchasing and sales process uses PHP and MySQL, so that financial accounting data can be managed appropriately and accurately. From the analysis and implementation process accounting information systems in purchasing and Sales process is to know accounting information system of purchase and sales process that can handle the item data management, purchasing, sales and financial report process.Keywords : Accounting Information Systems, Purchasing and Sales Process